Exploring the neuroprotective role of probiotics in the therapeutic interventions of cognitive decline - J Renukadevi; R Velmurugan; G Nandhinidevi; V S Karthikha; V Sri Vaishnavi (Creative Pharma Assent, 2024)
Background: Cognitive decline is developing as a critical alarm in public health concerns initiated by neuroinflammation, an indispensable contributing factor in neurodegenerative diseases. Probiotics and postbiotics have evolved as key therapeutic factors in treating neuroinflammation by modulating neuroinflammatory pathways and therapeutically controlling cognitive decline by its influence on the gut-brain axis. Methodology: This comprehensive review integrates the current status of the insight into the molecular mechanisms of probiotics that promote cognitive health. The review explains their synergistic effects on gut microbiota and their influence on neuroinflammation, mitochondrial function, neurotransmitter levels, and insulin sensitivity. It also explores preclinical and clinical studies involving the neuroprotective benefits of specific probiotic strains. Results: Probiotics are reported to alter gut microbiota by supporting neuroinflammation, thus enhancing cognitive function. The key findings were their role in reducing plaque formation and controlling tau protein hyperphosphorylation, thus improving mitochondrial efficiency. Recent research reveals that strains such as Lactobacillus and Bifidobacterium have proven efficacy in reducing tau phosphorylation and amyloid β pathology in animal models. In addition, probiotics improve insulin sensitivity and neurotransmitter levels, leading to improved cognitive outcomes. Discussion: The microbiota-gut-brain axis is essential in studying the neuroprotective role of probiotics. Probiotics have been reported for their ability to reduce neuroinflammatory markers, leading to improved neurogenesis in the brain's hippocampus. Thus transforming these research findings to clinical therapies requires further research to support and to overcome the limitations and exploring the complete mechanism involved. Conclusion: Probiotics thus being explored to develop as new therapeutic interventions in cognitive decline, with substantial preclinical evidence supporting their benefits. Still persistent research is essential to transform these findings in clinical trials in the development of probiotic-based therapies for cognitive health.